Andronikos I Komnenos: A Greek Tragedy - MAGOULIAS, Harry J. (Byzantina Symmeikta, 2011)
The Annals of Niketas Choniates depict Emperor Andronikos I Komnenos (1183-1185) in certain aspects of his lifestyle as a mirror image of his first cousin, Emperor Manuel I Komnenos (1143-1180). The life and death of Andronikos I Komnenos provide us with a window into the aesthetic, moral, intellectual, religious, economic and emotional world of Byzantine society in the 12th century. It was thanks to the Byzantine empire that the ancient texts were preserved and transmitted. Ancient Greek culture and reason, in particular, continued to inform Christian values while, at the same time, both could be in radical conflict. The tragic reign of Andronikos as presented by Niketas Choniates conforms to Aristotle’s principles of classical drama, but there is a fundamental disagreement between the author of the Poetics and the historian as to what constitutes tragedy, which underlines this conflict.